A study of usefulness of washes and brush cytology with respect to histopathology in diagnosis of lung malignancy by using fiberoptic bronchoscopy - Bandyopadhyay, Abhishek; Pal, Mallika; Das, Indranil; Sarkar, Supriya; Sarkar, Ranu; Taraphdar, Pranita (Clinical cancer investigation journal, 2016)
Background: Examination of specimens obtained through flexible fiberoptic bronchoscope is important and often the initial diagnostic technique performed in patients with suspected malignant lung lesion. Aims: To evaluate the usefulness of cytological findings of bronchial washings (pre-and post-bronchoscopy) and bronchial brushing in the diagnosis of lung malignancy with histopathology of bronchial biopsy, taking the latter as the confirmatory diagnostic test. Settings and Design: It was a cross-sectional observational study conducted in a tertiary care center. Subjects and Methods: A total of fifty patients with suspected lung malignancy (clinically and radiologically) were included in this nonrandomized cross-sectional study. Bronchial brushings were obtained from all fifty cases. Prebiopsy bronchial washing (washing collected before the brushing and biopsy procedure) and postbiopsy washing (washing at the end of the procedure) were collected. Results: Prebiopsy (prebrushing) and postbiopsy washing showed high specificity of 92.31%, but a very low sensitivity of 32.43% and 35.14%, respectively. Sensitivity and specificity of brushing were found to be 74.36% and 81.82%, respectively. Positive predictive value of prebiopsy (prebrushing) washing, postbiopsy washing and brushing are 92.31%, 93.55%, and 92.86%, respectively. There was no significant difference in sensitivity between prebiopsy (prebrushing) and postbiopsy washing (Fisher exact probability test; PA= 0.99). However, there was statistically significant difference between sensitivity of brushing with prebiopsy (prebrushing) washing (Fisher exact probability test; PA = 0.0012793) and postbiopsy washing (Fisher exact probability test; PA = 0.00310282). Conclusions: Bronchial washing cytology in combination with brush cytology aids in the early diagnosis of lung malignancy in addition to histopathology.